1997
DOI: 10.1093/protein/10.5.575
|View full text |Cite
|
Sign up to set email alerts
|

Importance of a conserved phenylalanine-35 of cytochrome b5 to the protein's stability and redox potential [published erratum appears in Protein Eng 1997 Aug;10(8):983]

Abstract: Phenylalanine-35, which is a residue of the hydrophobic patch on the surface of cytochrome b5, has been mutated into Tyr35, His35 and Leu35 to elucidate the functions of the Phe35 and give further insight into the roles of the hydrophobic patch and/or aromatic network. The effects of these mutations on the heme environment, denaturation towards heating and the denaturant urea, redox potential and stability of protein were studied. The relative stability of cytochrome b5 and its mutants towards heating has the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
20
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 2 publications
3
20
0
Order By: Relevance
“…Bovine liver cyt b 5 and its mutants were prepared and purified as described previously [13]. The concentrations of ferricytochrome b 5 and the mutants were determined with the value of OD 414 = 117 m m −1 ·cm −1 [16].…”
Section: Protein Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…Bovine liver cyt b 5 and its mutants were prepared and purified as described previously [13]. The concentrations of ferricytochrome b 5 and the mutants were determined with the value of OD 414 = 117 m m −1 ·cm −1 [16].…”
Section: Protein Preparationmentioning
confidence: 99%
“…In that study we found that of the three mutants, the Phe35→Tyr mutant displayed abnormal properties. The redox potential of the Phe35→ Tyr mutant is 66 mV more negative than that of the wild‐type cyt b 5 [14], and the oxidized Phe35→Tyr mutant is obviously more stable towards heat and chemical denaturation than wild‐type cyt b 5 [13]. We also studied electron transfer reactions of cyt b 5 Phe35→Tyr and Phe35→Leu variants with cytochrome c , with the wild‐type and the Tyr83Phe, Tyr83Leu variants of plastocyanin, and with the inorganic complexes [Fe(EDTA)] – , [Fe(CDTA)] – and [Ru(NH 3 ) 6 ] 3+ .…”
mentioning
confidence: 99%
“…Two His residues (His44 and His68) provide the fifth and sixth heme ligands (Figure 1A, B), and two propionate groups of the heme b lies at the opening of the heme-binding pocket, which is formed by highly conserved hydrophobic amino acid residues (Figure 1A). The roles of each amino acid were investigated by detailed site-directed mutagenesis in the past with employing various structural, spectroscopic and electrochemical techniques, including X-ray crystallography [18-20], NMR [21-23], UV-visible absorption spectroscopy, and redox potential measurements [24]. …”
Section: Introductionmentioning
confidence: 99%
“…Cyt b 5 can be proteolyzed by trypsin to produce a soluble N-terminal fragment consisting of 84 residues which is termed Tb 5 , whereas lipase can proteolyze the protein to produce a 93-residue fragment referred to as Lb 5 (6). The stability of cyt b 5 has been studied by heat (7)(8)(9) and denaturants (9). For example, the heme of cyt b 5 has been shown to dissociate from the protein by denaturing the protein with urea, and the denaturant concentration and temperature for dissociation of the heme have been used to estimate the protein stability (9).…”
mentioning
confidence: 99%
“…The stability of cyt b 5 has been studied by heat (7)(8)(9) and denaturants (9). For example, the heme of cyt b 5 has been shown to dissociate from the protein by denaturing the protein with urea, and the denaturant concentration and temperature for dissociation of the heme have been used to estimate the protein stability (9).…”
mentioning
confidence: 99%